Implementation of PCC Load Balancing and Failover Using Mikrotik CHR on Virtual GNS3 - Abraara, Novellza Arfedin; Islamiyah, Mufidatul (LP2M Institut Teknologi dan Bisnis ASIA Malang, 2026)
The rapid development of network technology demands a reliable, efficient system capable of providing continuous, uninterrupted service. One important aspect of achieving this goal is implementing a load-balancing method that distributes network traffic evenly. In this study, a PCC (Per Connection Classifier) was designed and integrated with a failover mechanism to improve network performance and availability. The PCC method is used to dynamically divide traffic based on connections, while the failover mechanism functions as an automatic backup system in the event of disruption to the main path. The design results indicate that combining PCC and failover can increase reliability, improve load distribution, and minimize downtime in the network structure. This implementation is expected to serve as a reference for the development of a more stable and efficient network infrastructure. Test results show that applying the PCC and failover method can increase average throughput by up to 35%, reduce latency by 20%, and accelerate connection recovery, with an average failover time of under 3 seconds. Thus, this design is proven effective in improving network reliability and internet service quality in multi-gateway systems